Two little girls : a novel - Jarratt, Laura (Sourcebooks Landmark, 2022)
"Two girls. One chance. When Lizzie's car crashes with her two daughters inside, she faces a terrible choice. And when she recovers from her injuries, she has to deal with the impact of that tragedy as well as the police investigation into it. As Lizzie and her family struggle to come to terms with the events of that night, things take an even darker turn. What exactly happened on that remote country road? Who is responsible? And can the family get through this together... or will the truth finally tear them apart? Two Little Girls is an unputdownable page-turner that takes us deep inside the secret life of a family with plenty to hide, and the unthinkable choice that one mother is forced to make."--